Monitoring of Reading Comprehension Across the First, Second, and Third Language: Domain‐General or Language‐Specific?. Issue 3 (20th May 2020) - Silawi, Razan; Shalhoub‐Awwad, Yasmin; Prior, Anat
Abstract: This study examined the monitoring abilities of trilinguals in reading comprehension, addressing the following questions: Is comprehension monitoring related to reading comprehension across first, second, and third languages? Is comprehension monitoring shared across the languages of trilingual adults (domain‐general) or rather linked to language proficiency (language‐specific)? Eighty undergraduates, trilingual in Arabic, Hebrew, and English, read three texts in each language, answered multiple‐choice questions, and rated their confidence in their responses. From this we derived the absolute and relative accuracy of monitoring. The results showed links between accurate monitoring and successful comprehension in all the languages of participants, but these were weaker in English, the least proficient language. Further, the results lend some support to the involvement of both domain‐general and language‐specific processes in comprehension monitoring. Specifically, monitoring seems to be utilized similarly by individuals to support comprehension across the first and second languages, but is less well generalized to the third language. Abstract :